Generalized DEMATEL technique with centrality measurements - Chen, Chin-Yi; Tzeng, Gwo-Hshiung; Huang, Jih-Jeng (Technological and Economic Development of Economy, 2018)
DEMATEL technique is a useful tool for understanding the influential relationship between criteria of a systematic problematique in structural modeling, and has received much attention in the field of decision analysis recently. However, the past papers focused on the applications of DEMATEL technique and ignored the convergence problem of the approach. In addition, two simple indicators, i.e., in-degree and out-degree centralities, used in DEMATEL technique cannot fully represent the insight of the network relationship. In this paper, we propose a general DEMATEL technique which incorporated the concept based on interaction diminishing effect. The traditional DEMATEL technique can be considered as a special case of the proposed method when we ignore the effect. Later, we give six important indicators which can be used in DEMATEL technique to conclude the relative importance of criteria. In addition, a numerical example is used to demonstrate the proposed method and the applications of the indicators.First published online: 08 May 2017